Graphene oxide–porphyrin composite nanostructure included electrochemical sensor for catechol detection. (12th January 2021) - Ören Varol, Tuğba; Hakli, Ozgul; Anik, Ulku
Abstract : A novel composite nanostructure (GO–Por) has been prepared via ultrasonication and exhibited enhanced electrocatalytic activity towards catechol oxidation. Abstract : In this study, pre-synthesized 5, 10, 15-tri(4- tert -butylphenyl)-20-(4-phenol)-porphyrin (Por) was incorporated with graphene oxide (GO) via ultrasonication and, as a result, GO–Por was obtained. Morphological and structural characterizations of GO–Por were performed using scanning electron microscopy, Fourier transform infrared spectroscopy and ultraviolet-visible spectroscopy, demonstrating that the porphyrin derivative was attached to GO. The resulting GO–Por composite was utilized as the modifier for the construction of a carbon felt based electrochemical catechol sensor. The GO–Por modified sensor exhibited a nearly 10-fold increment in the oxidation peak current accompanying a 31 mV negative shift in the oxidation potential as compared with the unmodified sensor. A linear response in the range of 5–250 μM catechol with a limit of detection of 0.063 μM ( n = 3) was obtained with the proposed method. The GO–Por modified carbon felt sensor was also applied for catechol detection in tap water samples and very satisfactory recovery values were obtained.